A benefit evaluation for recycling medical plastic waste in China based on material flow analysis and life cycle assessment. (25th September 2022) - Liu, Manzhi; Wen, Jixin; Feng, Ying; Zhang, Linlin; Wu, Jixin; Wang, Jinfeng; Yang, Xiaotao
Abstract: Recycling medical plastic waste has the potential to significantly reduce environmental pollution while also providing significant economic benefits. This study develops a benchmark model for the benefit evaluation of China's medical plastic waste recycling decision system in 2019, focusing on the recovery system's benefits and costs. Following model construction, a sensitivity analysis is conducted on the relevant parameters affecting the recycling system's efficiency. Finally, the system's primary recovery indexes are predicted for three development scenarios based on the results of sensitivity analysis: low-speed, medium-speed, and high-speed development. The results indicate that each ton of medical plastic waste generates an economic benefit of 2708.6 yuan in 2019, 187.8 μg TEQ of dioxin during incineration, and 1.48 tons of carbon dioxide during the recovery process. The total emission reduction is approximately 0.76 tons when compared to the initial production. If the illegal recovery rate is reduced by 0.5% and the mixed disposal rate is reduced by 5%, the comprehensive benefits increase by approximately 15.3% and 2.2%, respectively. The results of the scenario simulations indicate that the recovery benefit and potential for emission reduction associated with each ton of medical plastic waste increase year after year, while carbon dioxide emissions exhibit an inverted "U" shape evolution. Graphical abstract: Image 1 Highlights: Material flow analysis and LCA for medical plastic recycling system is constructed. Benefits and losses of the recycling system are analyzed quantitatively. The sensitivity analysis of three main factors affecting the system is carried out. The recovery benefits are predicted under scenarios of low, mid and high speed. Recycling makes the safe disposal of medical waste and brings considerable benefits.